Validation of a finite element model with six-year-old child anatomical characteristics as specified in Euro NCAP Pedestrian Human Model Certification (TB024). Issue 1 (20th May 2021) - Li, Haiyan; Li, Kun; Huang, Yongqiang; Lv, Wenle; Cui, Shihai; He, Lijuan; Ruan, Jesse Shijie; Wang, Chunxiang
Abstract: Accident statistics show that more than 80% of car-to-pedestrian collisions (CPC) occur when pedestrians cross the road. It is very important to establish a finite element model with natural walking posture to study the kinematics and injury mechanism of pedestrians. In this study, a finite element model of six-year-old child pedestrian is developed with detailed anatomical characteristics and posture parameters as specified in Euro NCAP Pedestrian Human Model Certification (TB024). The numerical human body model is validated in total twelve simulations in which the pedestrian is impacted against four generic vehicle models at speeds 30, 40, 50 km/h prescribed in TB024. The Head Impact Time (HIT), Contact Force and the Trajectories of HC, T12 and AC of all twelve simulations are compared with the reference corridors provided by Technical Bulletin 024. The results indicate that the numerical human body model of a six-year-old child can be used to demonstrate the suitability of the sensing system for the range of pedestrian sizes; the timing of system deployment, and the bonnet deflection due to body loading. Furthermore, the model could be a good tool for further research on pedestrian injury mechanism and the development of pedestrian protection devices.